Analytical Method Development of Content and Dissolution Assay of Ursodeoxycholic Acid Capsule - Wanti Megawati; Sophi Damayanti (Indonesian Journal of Pharmaceutical Science and Technology, 2021)
Ursodeoxycholic acid is an active compound to treat cholesterol gallstones which is included in Biopharmaceutical Classification System class II. Ursodeoxycholic acid capsule formulations have been developed by the pharmaceutical industries. Due to requirement, active ingredient testing and dissolution tests need to be routinely carried out to control quality of the drug. Therefore, aim of this study was to develop a simultaneously analytical method for assay and dissolution test. Optimum condition of analysis were using HPLC-RID, C18 column (5 µm; 3.9 x 300 mm), flow rate 1 mL/min, 50 µL volume injection, acetonitrile:buffer phosphate pH 3.0 (55:45 v/v) as mobile phase, column, detector, and sample temperature were 40 oC. This method provides good linearity in a range of 50-130 % concentration for assay and dissolution test with correlation coefficient values of 1 and 0.9995, respectively. LOD and LOQ for assay were in value of 4.892 µg/mL and 14.824 µg/mL whereas for dissolution tests in a value of 6,501 µg/mL and 19,701 µg/mL. The average percent recovery for assay and dissolution test were in a range of 100.018±0.888% and 98.936±2.124 %. Repeatability and intermediate precision of assay were obtained by determining RSD values of 0.466% and 0.279-0.483 %, while the dissolution test were 1.137% and 0.032-0.289 %. The validation show this method are linear, selective, accurate, and precise.Keywords: Assay, dissolution test, Ursodeoxycholic acid, validation